2000
DOI: 10.1155/2000/172914
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Celiac Disease in Girls with Turner Syndrome Detected Using Antibodies to Endomysium and Tissue Transglutaminase

Abstract: One girl with TS was identified with CD from 45 screened, giving an overall biopsy-confirmed prevalence of 2.2%. This study confirms previous observations placing girls with TS at higher risk for CD and suggests a similar high prevalence in British Columbia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
(10 reference statements)
1
20
0
Order By: Relevance
“…The prevalence of CD observed in this group of females with TS (3.6%) was lower than the prevalence of 6.4% reported by Bonamico et al (4) but similar to the prevalence found in other studies, varying from 2.2 to 5.0% (8,12,13) . Some of those studies have shown that part of the diagnosed patients were asymptomatic or presented atypical forms of CD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prevalence of CD observed in this group of females with TS (3.6%) was lower than the prevalence of 6.4% reported by Bonamico et al (4) but similar to the prevalence found in other studies, varying from 2.2 to 5.0% (8,12,13) . Some of those studies have shown that part of the diagnosed patients were asymptomatic or presented atypical forms of CD.…”
Section: Discussionsupporting
confidence: 85%
“…Other less frequently reported autoimmune disorders include inflammatory bowel disease (9,17) and idiopathic juvenile arthritis (33,34) . Since the last decade, an increasing number of studies have also demonstrated a higher prevalence of celiac disease (CD) among females with TS when compared with the general population (4,10,12,13,21) .…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholine receptor antibodies were measured using a modified radioimmunoprecipitation assay [6] . Approval to test samples for endomysial antibodies and IgA tissue transglutaminase antibody concentrations was obtained through the Clinical Research Ethics Board at UBC as previously noted [7,8] .…”
Section: Special Serological Studiesmentioning
confidence: 99%
“…The diagnosis of celiac disease should be excluded in patients with irritable bowel syndrome (9). Conditions with an increased risk of developing celiac disease include Type I diabetes (3,(10)(11)(12)(13)(14), autoimmune thyroiditis (3,15), Down syndrome (3,(16)(17), Turner syndrome (3,18), Williams syndrome (19), selective IgA deficiency (3,20,21), and being a first or second degree relative of affected individuals (22,23) (Table 2). Families with two or more affected siblings are at the highest risk; up to 26% for siblings and 13% for parents (22).…”
Section: Clinical Manifestations Andmentioning
confidence: 99%